2011
DOI: 10.1186/1471-2148-11-159
|View full text |Cite
|
Sign up to set email alerts
|

The two tryptophans of β2-microglobulin have distinct roles in function and folding and might represent two independent responses to evolutionary pressure

Abstract: BackgroundWe have recently discovered that the two tryptophans of human β2-microglobulin have distinctive roles within the structure and function of the protein. Deeply buried in the core, Trp95 is essential for folding stability, whereas Trp60, which is solvent-exposed, plays a crucial role in promoting the binding of β2-microglobulin to the heavy chain of the class I major histocompatibility complex (MHCI). We have previously shown that the thermodynamic disadvantage of having Trp60 exposed on the surface is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Given that an intact adaptive immune response is vital for life in all higher eukaryotes, there is immense evolutionary pressure on the sequences of both the MHC-1 heavy chain and β 2 m to ensure that they fold and bind efficiently. This explains why the sequence of β 2 m is so highly conserved from cartilaginous fish to humans 83 and why the smallest changes to its sequence that cause the isomerization of a single peptide bond can lead to aggregation and disease. In addition, the interactions between β 2 m and the MHC-1 heavy chain have coevolved in such a way as to minimize aggregation risks, although the susceptibility is ever present when the fragile fold of β 2 m is left on its own.…”
Section: The Dangerous Plasticity Of An Immunoglobulin Foldmentioning
confidence: 99%
“…Given that an intact adaptive immune response is vital for life in all higher eukaryotes, there is immense evolutionary pressure on the sequences of both the MHC-1 heavy chain and β 2 m to ensure that they fold and bind efficiently. This explains why the sequence of β 2 m is so highly conserved from cartilaginous fish to humans 83 and why the smallest changes to its sequence that cause the isomerization of a single peptide bond can lead to aggregation and disease. In addition, the interactions between β 2 m and the MHC-1 heavy chain have coevolved in such a way as to minimize aggregation risks, although the susceptibility is ever present when the fragile fold of β 2 m is left on its own.…”
Section: The Dangerous Plasticity Of An Immunoglobulin Foldmentioning
confidence: 99%
“…Although frequent transitions to the unfolded state of β 2 m are likely to allow increased kinetic sampling of aggregation‐competent conformations, we have shown here that this is not sufficient to enable nucleation of β 2 m fibril formation at neutral pH. It has been suggested that conformational flexibility is dampened by evolution to reduce the potential risk of aggregation as described above . Here we show that monomeric β 2 m displays unusually high kinetic instability for an immunoglobulin domain, presumably because the evolutionary pressure on its sequence has been to enable tight binding to the MHC heavy chain.…”
Section: Discussionmentioning
confidence: 66%
“…It has been suggested that conformational flexibility is dampened by evolution to reduce the potential risk of aggregation as described above. [52] Here we show that monomeric b 2 m displays unusually high kinetic instability for an immunoglobulin domain, presumably because the evolutionary pressure on its sequence has been to enable tight binding to the MHC heavy chain.…”
Section: The Probability Of Global Unfolding Does Not Correlate With mentioning
confidence: 74%
“…In addition, this new analysis reveals the population of solvent-exposed conformations of D76N β2m W95 side-chain, in both protein states. The position of W95 is central in β2m hydrophobic core and its mutation greatly destabilises the protein fold (21,34). It is likely that β2m conformations with an exposed W95 may be highly destabilised and may represent an important step in the foldingunfolding pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The high-energy state M 1 * was suggested to be associated with protein misfolding and consequently with aggregation (16,32,33). Conversely, given the pivotal role of W95 in the stability of β2m buried hydrophobic core (21,34), one may speculate that excited state M 2 *, having a highly solvent exposed W95 residue, may be associated with protein folding-unfolding and consequently with thermodynamic stability.…”
Section: Nmr-restrained Molecular Dynamics: Comparison Between Conformentioning
confidence: 99%